2021
DOI: 10.1155/2021/2202888
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-137 Inhibited Hypoxia-Induced Proliferation of Pulmonary Artery Smooth Muscle Cells by Targeting Calpain-2

Abstract: The proliferation of pulmonary artery smooth muscle cells (PASMCs) is an important cause of pulmonary vascular remodeling in pulmonary hypertension (PH). It has been reported that miR-137 inhibits the proliferation of tumor cells. However, whether miR-137 is involved in PH remains unclear. In this study, male Sprague-Dawley rats were subjected to 10% O2 for 3 weeks to establish PH, and rat primary PASMCs were treated with hypoxia (3% O2) for 48 h to induce cell proliferation. The effect of miR-137 on PASMC pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…MiR-124-3 reduces cardiomyocyte viability by increasing the expression of the target calpain1, enhancing caspase-3 activity and down-regulating Bcl-2 (137). MiR-137 suppresses the proliferation of hypoxia-induced PASMC and improved PAH by upregulating calpain-2 expression (138). Moreover, Gao, Chen et al (139) found that many miRNAs promote cardiomyocyte autophagy and improve cardiac function by upregulating ATGs (LC3 and beclin-1) and generating autophagosomes.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-124-3 reduces cardiomyocyte viability by increasing the expression of the target calpain1, enhancing caspase-3 activity and down-regulating Bcl-2 (137). MiR-137 suppresses the proliferation of hypoxia-induced PASMC and improved PAH by upregulating calpain-2 expression (138). Moreover, Gao, Chen et al (139) found that many miRNAs promote cardiomyocyte autophagy and improve cardiac function by upregulating ATGs (LC3 and beclin-1) and generating autophagosomes.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…MiR-124-3 reduces cardiomyocyte viability by increasing the expression of the target calpain1, enhancing caspase-3 activity and down-regulating Bcl-2 ( 137 ). MiR-137 suppresses the proliferation of hypoxia-induced PASMC and improved PAH by upregulating calpain-2 expression ( 138 ). Moreover, Gao, Chen et al.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Of note, MYC can also influence the activation of mTOR pathway by regulating the metabolic reprogramming of glutamine ( 71 , 72 ). Although the specific contribution of MYC to the metabolic disturbance of PH has not been elucidated, it has been found that MYC activation is related to the proliferation of PAECs and PASMCs ( 5 , 73 ). In addition, recombinant interleukin-6 (IL-6) treatment in rodent models under hypoxia led to pulmonary vascular remodeling, at least in part by MYC activation ( 74 , 75 ).…”
Section: Glutamine Metabolism In Pulmonary Hypertensionmentioning
confidence: 99%